Analysis of pressure and pressure derivative interference tests under linear and spherical flow conditions (2018)
Often, interpretation of interference tests is performed for systems acting under radial flow regimen conditions by means of conventional straight-line method, type-curve matching and TDS technique. For linear and spherical flow cases, the interpretation of interference tests is performed by the conventional analysis and type-curve matching. These procedures do not allow verification of the estimated parameters; therefore, this paper presents the formulation of a more practical, useful and accurate methodology which is achieved based upon the determination of characteristic features found on the pressure and pressure derivative versus time log-log plot with the purpose of developing analytical expressions for the interpretation of interference tests under spherical and linear flow conditions. These equations were successfully verified by their application on synthetic tests.